Legal Consequences Against Forgery of Signatures in the Deed of Sale and Purchase Issued by the Land Deed Maker's Office (PPAT) - Fakhriansyah, Rizky (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The Land Deed Making Official as the official authorized to issue the Authentic Deed is obliged to examine the correctness of the documents that are a requirement in the issuance of the Sale and Purchase Deed. In practice, there are Land Deed Making Officials who ignore the obligation to examine the documents brought by the appearers as in the case of Muslim in Decision Number 538/Pid.B/2019/PN.Pdg where there is forgery of signatures by the parties in the approval of the making of the Deed. Sale and Purchase, the statement of the reporting witness which was later corroborated by the results of the criminalistic laboratory examination showed that the signature in the Sale and Purchase Deed was declared non-identical to the actual signature, as a result the Sale and Purchase Deed caused losses to the other party. Based on these problems, it raises the question of what are the legal consequences of the proof of falsification of signatures in the Sale and Purchase Deed issued by the Land Deed Making Official and how the Land Deed Maker Officer applies the precautionary principle in making the Sale and Purchase Deed. The research method used is normative juridical research using a law approach and a case approach using data collection methods through documentation studies and literature studies on court decisions. The results of the research are that if the deed of sale and purchase occurs forgery of signatures, the certificate and deed of sale and purchase are declared null and void. A Land Deed Official in making an authentic deed must pay attention to the principle of prudence, one of which is by requiring the parties to be present in person and check the authenticity of the parties' identities in order to prevent identity